(World) Literature (translation. a transdisciplinary journal, 2022)
Once we start to consider the way in which both the terminology of translation and the idea of authentic ‘original’ that exits somewhere beyond the text in front of us are used by writers, then the question of when a translation is or is not taking place becomes increasingly difficult to answer. It is probably more helpful to think of translation not so much as a category in its own right, but rather as a set of textual practices with which the writer and reader collude.